Protocol for synthesizing, implanting, and using polydimethylsiloxane as skull replacement in mice for imaging, electrophysiology, and optogenetics - Kengo Takahashi; Gerjan Huis in ‘t Veld; Davide Benedetti; Jun-Ying Wang; Samuel Pontes Quero; Rafael Yuste; Cyriel M.A. Pennartz; Umberto Olcese (STAR Protocols)
Summary: Many techniques to record and manipulate neuronal activity across large portions of the vertebrate brain are now available. However, few effective approaches enable both optical and mechanical access to the brain. Here, we present a protocol for synthesizing, implanting, and using polydimethylsiloxane (PDMS) windows as skull replacements for chronic wide-field and two-photon calcium imaging in mice. We also describe steps for performing viral injections and multi-site silicon probe implantation. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.